Pollen morphology of Proteaceae native to Argentina: a new dichotomus key for their identification - Fernández, Damián Andrés (2017)
A dichotomous key for the identification of eight proteaceous species, native to Argentina, based on pollen morphology is presented. These species are: Embothrium coccineum, Gevuina avellana, Lomatia dentata, L. ferruginea, L. hirsuta, Orites myrtoidea, Roupala meisneri and R. montana. The pollen morphology was analyzed with both, light and electron scanning microscopes. The morphological characters selected for species/ genera recognition are: ornamentation, pore number, equatorial diameter, the ratio of sexine/nexine thickness, and equatorial diameter/pore diameter ratio.